Diffusion of information technology, internet use and the demand of heterogeneous labor - Martin Falk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper analyzes the link between the diffusion of information- and communication technology (ICT) and both the skill structure and employment expectations of the different skill categories. The analysis is based on cross-sectional data for 4150 German firms conducted in mid-2000. The penetration of ICT is measured as the percentage of workers using a computer on the job for at least half of the working time, the number of computers per worker, percentage of workers with internet access, as well as the use of software applications such as ERP, CAD/CAE and database management systems. The empirical evidence indicates that firms with a higher diffusion of ICT employ a larger fraction of workers with a university degree as well as ICT specialists. Conversely, a greater ICT penetration is significantly negatively related to the share of both medium-skilled and unskilled workers. To account for censoring in the employment shares, the empirical analysis uses Powell?s (1984) Censored Least Absolute Deviations estimator (CLAD). Furthermore, results of ordered probit models show that employment expectations for workers with a university degree are positively related to the degree of ICT penetration.
Keywords: L80; O33; J23; C24; 330; diffusion of information technology; labor demand; skill structure; censored regression model; Informationstechnik; Computergestütztes Verfahren; Innovationsdiffusion; Arbeitsnachfrage; Qualifikation; Hochqualifizierte Arbeitskräfte; Beschäftigungseffekt; Schätzung; Deutschland